Peripheral Pulmonary Artery Stenosis as a Cause of Pulmonary Hypertension in Adults. (March 2015) - Tonelli, Adriano R.; Ahmed, Mostafa; Hamed, Fadi; Prieto, Lourdes R.
Peripheral pulmonary artery stenosis (PPAS) is an underrecognized condition in the adult population. PPAS can lead to pulmonary hypertension but is likely misdiagnosed as either idiopathic pulmonary arterial hypertension or chronic thromboembolic pulmonary hypertension. We retrospectively identified adult patients with PPAS either in its isolated form or related to other congenital defects from January 1998 to September 2012. We reviewed the patients' clinical data by using our hospital electronic medical records and/or their paper charts. We identified 6 adult patients with PPAS with an age range of 16–56 years (1 woman and the rest men). Presenting signs and symptoms were thoracic murmurs, progressive dyspnea, and syncope. Three patients had Williams-Beuren syndrome. Pulmonary angiography showed that PPAS was predominantly located in main branches or lobar pulmonary arteries in 5 patients, while in 1 patient the arterial narrowing was at the level of the segmental pulmonary arteries. Right heart catheterization showed a mean pulmonary artery pressure (PAP) ranging from 35 to 60 mmHg. Balloon dilation was performed in all patients, predominantly in the lobar arteries, and it caused a decrease in mean PAP that ranged from 16% to 46% in 5 patients. In 1 patient the mean PAP did not decrease. All but 1 patient had follow-up echocardiograms at 1 year that showed stable echocardiographic findings. Pulmonary hypertension due to PPAS continues to presents a diagnostic challenge. Therefore, a high index of suspicion during the initial evaluation of pulmonary hypertension is essential for its prompt diagnosis and adequate treatment.